Transcriptome-wide characterization of bHLH transcription factor genes in Lycoris radiata and functional analysis of their response to MeJA - Wang, Ning; Shu, Xiaochun; Zhang, Fengjiao; Wang, Zhong (Frontiers in Plant Science, 2023)
As one of the biggest plant specific transcription factor (TF) families, basic helix–loop–helix (bHLH) protein, plays significant roles in plant growth, development, and abiotic stress responses. However, there has been minimal research about the effects of methyl jasmonate (MeJA) treatment on the bHLH gene family in Lycoris radiata (L’Her.) Herb. In this study, based on transcriptome sequencing data, 50 putative L. radiata bHLH (LrbHLH) genes with complete open reading frames (ORFs), which were divided into 20 bHLH subfamilies, were identified. The protein motif analyses showed that a total of 10 conserved motifs were found in LrbHLH proteins and motif 1 and motif 2 were the most highly conserved motifs. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of LrbHLH genes revealed their involvement in regulation of plant growth, jasmonic acid (JA) mediated signaling pathway, photoperiodism, and flowering. Furthermore, subcellular localization revealed that most LrbHLHs were located in the nucleus. Expression pattern analysis of LrbHLH genes in different tissues and at flower developmental stages suggested that their expression differed across lineages and might be important for plant growth and organ development in Lycoris. In addition, all LrbHLH genes exhibited specific spatial and temporal expression patterns under MeJA treatment. Moreover, protein-protein interaction (PPI) network analysis and yeast two-hybrid assay showed that numerous LrbHLHs could interact with jasmonate ZIM (zinc-finger inflorescence meristem) domain (JAZ) proteins. This research provides a theoretical basis for further investigation of LrbHLHs to find their functions and insights for their regulatory mechanisms involved in JA signaling pathway.